THE EMPLOYEES MOTIVATION WITHIN AN EVENT ORGANIZING COMPANY DURING COVID-19 PANDEMIC : STUDY OF EVENTX - Rani Candra Kurniawati; Anggara Wisesa (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The entire economy in Indonesia experienced turmoil and decline due to the spread of the Covid-19 virus. Likewise, the event organizer industry also experienced a decline. All event organizer companies are having a hard time. Employee motivation at work is affected by internal and external factors, caused by dispositional factor or internal, such as personality trait, effort, mood, judgment, ability, motive, belief and situational factor or external, such as world’s phenomenon, other’s people attitude, time of day, task difficulty, and luck. This study analyzes employee motivation affected by dispositional and situational factors and influences employee performance while working in Event Organizer during Covid-19 Pandemic. This study uses a qualitative approach with attribution theory and phenomenological method. Researcher conducts semi-structured interviews with three employees of the EventX company. The result of this study is the understanding of the factors that significantly influence the employee motivation of EventX through two approaches, dispositional and situational. The researcher found that there are changes in motivation and affect performance during the Covid-19 pandemic. This study will become a reference to increase motivation levels, especially for event industry amid the Covid-19 situation and enhance employee performance.